The Integration of European and Asian Stock Exchanges: Federation of Euro-Asian Stock Exchanges - Rosińska, Magdalena (Integracja giełd papierów wartościowych Europy i Azji na przykładzie organizacji Federation of Euro-Asian Stock Exchanges, 2010)
The integration of capital markets has a significant meaning for economy development. When capital markets are associated, they are better managed and the capital flow is wider. Because of well developed capital market the level of savings in economy grows, and it gives opportunity to allocate them in productive investments - and this is the source of economical growth, which is very important in the times of financial crisis. The advantages of capital markets cooperation and integration are available for European and Asian stock exchanges because of the existence of Federation of Euro-Asian Stock Exchanges (FEAS). This organization promotes the development of emerging stock markets in Europe and Asia by supporting each other and exchanging experiences.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 132-142
Keywords: financial integration; capital markets cooperation; capital flow; capital markets managing